THE IMPORTANCE OF THE IMPLEMENTATION OF DRAMA AND CULTURE IN SPEAKING CLASS - Budiarto Budiarto (Journal of English Language and Literature (JELL), 2020)
A research conducted at STIBA IEC Jakarta investigated the importance of the implementation of drama and culture in Speaking Class of students from the second semester in 2018. It was intended to see how the phenomena of teaching English speaking skill through drama and culture was implemented. The findings indicated that drama and culture were able to help the students use English more naturally or authentically. The students were able to see whether their English was authentic and culturally acceptable by relating to their experience or knowledge they got from drama. It showed that the more topics in drama the students practiced, the more knowledge about culture they learnt, and the more authentic or natural the language they acquired. Therefore, both teacher and students think that the implementation of drama and culture in teaching speaking skill is important.